Modality-specific somatosensory changes in a human surrogate model of postoperative pain - Fißmer, Ina; Klein, Thomas; Magerl, Walter; Treede, Rolf-Detlef; Zahn, Peter K.; Pogatzki-Zahn, Esther M. (Anesthesiology, 2011)
Postoperative pain remains a challenging problem in part because the underlying mechanisms are still not well understood. There is a compelling need for translational studies in human models of postoperative pain to bridge the gap between animal models und human clinical studies.Somatosensory changes using Quantitative Sensory Testing for up to 72 h after an experimental 4-mm incision were characterized in 20 male volunteers.During incision, perceived pain was 29 on a 100-point numeric rating scale and declined rapidly over the next 60 min. After incision, thresholds at the site of incision were lowered to painful heat (primary heat hyperalgesia; P < 0.01, effect size: 0.68) but not to painful cold (P > 0.05, effect size: 0.00). Remote to the incision, mechanical pain thresholds were lowered, pain ratings were increased, and an area of hyperalgesia occurred (P < 0.05, effect size: 0.56; P < 0.01, effect size: 0.70; P < 0.01, respectively; secondary mechanical hyperalgesia). All signs of heat and mechanical hyperalgesia declined until full resolution at 27-72 h after incision. Increased mechanical pain ratings remote to the incision (r = 0.47; P < 0.01) but not the area of hyperalgesia (r = 0.28) or heat hyperalgesia (r = 0.12) correlated with incision-induced pain.Ongoing activity of nociceptors underlying nonevoked pain after incision in humans may not be explained by sensitization of nociceptors to heat but triggers the increased painfulness of mechanical stimuli in the area of secondary hyperalgesia. However, the spatial expansion of hyperalgesia seems to rely on at least partly different mechanisms. These findings may contribute to the understanding of pain and hyperalgesia after surgery.
Gesehen am 11.05.2023